How Public Libraries are Keeping Pace with the Times: Core Services of Libraries in Informational World Cities - Christian Born; Maria Henkel; Agnes Mainka (Libri, 2018)
Abstract In a survey of 31 informational world cities, we investigate the state of the art public library core services. For this study, we applied the core service catalog developed by (Mainka, A., S. Hartmann, L. Orszullok, I. Peters, A. Stallmann, and W. G. Stock. 2013. “Public Libraries in the Knowledge Society: Core Services of Libraries in Informational World Cities.” Libri 63 (4): 295–319. 10.1515/libri-2013-0024), counted the services offered by the libraries and compared findings with the results from 2013, allowing us to calculate a score for each library and rank them accordingly. An overall improvement of the range of services was observed, with North American libraries taking the top three positions in the ranking. To get a clearer picture of the challenges facing libraries today, personal interviews were also conducted with (chief) librarians, especially concerning developments such as maker spaces, increasing demand for information literacy instruction and the changing role of physical library space. The results presented in this paper highlight best practice examples of library services in prototypical cities of the knowledge society.